Patient Safety Culture in Hospital Settings for Quality Improvement: A Cross-Sectional Assessment - Brury Apriadi Husaini; Rosa Galica Gita Gressia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Patient safety culture is a critical component of healthcare quality and plays an essential role in reducing medical errors. Understanding healthcare professionals’ perceptions of patient safety is important for identifying strengths and areas requiring improvement within hospital systems. Objective: This study aimed to assess patient safety culture among hospital staff in a single private hospital to support quality improvement initiatives. Methods: A quantitative cross-sectional study was conducted among 217 hospital staff working in both clinical and non-clinical units in a single private hospital. Data were collected using the Hospital Survey on Patient Safety Culture. Data were analysed using descriptive statistics to calculate frequencies, percentages, and percent positive responses for each dimension. Results: The findings showed moderate variation across patient safety culture dimensions. The highest positive response was observed in response to error (73.5%), followed by handoffs and information exchange (68.7%). Other dimensions, including communication about error (64%), staffing and work pace (63.5%), communication openness (63%), teamwork (62%), and overall patient safety rating (62%), also reflected moderate perceptions. However, reporting patient safety events had the lowest positive response (43%), indicating a potential gap in incident reporting practices. Conclusion: Overall, patient safety culture in this setting demonstrates moderate positive perceptions across several dimensions. However, the relatively low score in incident reporting suggests that this area may require further attention. These findings highlight the need for continued evaluation of reporting practices to better understand underlying barriers and support ongoing quality improvement efforts